The Toxic Effects of Low Molecular Weight Components of Cow Colostrums: The Short-Term and Long-Term Effects - Bozhkov, A.I.; Ivanov, E.G.; Kurguzova, N.I.; Alsardia, Muhammad M.A.; Akzhigitov, R.A.; Baranikova, S.Ya.; Potapova, V.I.; Chuprikova, A.S. (Journal of Nutritional Therapeutics, 2021)
Background: Low-molecular components of colostrum (LMWCC) have a pronounced biological activity. We investigated the effect of different doses of LMWCC (0.01, 0.1, 1 and 5 g/100 g of body weight) on the behavior, dynamics of growth, acute and chronic toxicity, as well as the relative weight of the liver, spleen and kidneys of the experimental animals. Methods: We used 100 3-month male rats in the experiment. All animals were divided into 5 groups of 20 animals in each group, LMWCC was administered per os, and the control group received sterile water. Results: LMWCC revealed no pirogenic effect in a wide diapason of doses (0,01-5 g/100 g of animal mass). Immediately after the LMWCC administration the short-time decrease in the motion activity was observed. The low doses of LMWCC induced diarrhea in 10-20 % of of animals, the super-large dose – in 75% of animals. The acute toxicity of LMWCC (death of 15 % of animals) was detected only in super-large dose of LMWCC and it was accompanied by pronounced diarrhea. LMWCC influenced the mass of liver, spleen and kidney. 60 days after LMWCC administration the mass of liver was restored to control weight, but the mass of spleen and kidney was not restored. Conclusion: LMWCCdo not have chronic toxicity and can be attributed to non-toxic compounds with a possible side effect - a violation of the digestive system.